Transformasi Digital Pengelolaan Keuangan Daerah dalam Mewujudkan Agile government pada Reformasi Birokrasi 4.0 - Rahmadany, Andi Fitri (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2024)
Various issues in regional financial management that remain suboptimal hinder the effectiveness, efficiency, transparency, and accountability of public service delivery. Therefore, the objective of this research is to analyze how digital transformation in regional financial management can support the creation of agile government within the context of bureaucratic reform 4.0. The research employs a descriptive method with a literature study design, utilizing descriptive analysis techniques. The findings indicate that the digital transformation of regional finances is not yet optimal, still hampered by a lack of understanding and training for officials, as well as disparities in technological infrastructure and challenges such as resistance to change and insufficient infrastructure. Overall, digital transformation and agile government mutually reinforce efforts toward bureaucratic reform and the enhancement of public service quality in Indonesia. A strategic approach to optimizing the digital transformation of regional financial management to achieve agile government in bureaucratic reform 4.0 emphasizes the creation of a new bureaucratic culture that is responsive, agile, and intelligent, along with competent human resources, effective work programs, and the rapid achievement of maximum results supported by the integration of technology. This approach is represented through technological innovation, collaboration, a focus on public service quality, training, sustainability and adaptation, as well as regular monitoring and evaluation. It is recommended that local governments collaboratively establish a forum for accelerating the digital transformation of regional financial management across stakeholders, involving the participation of various community elements.